KEABSAHAN PUTUSAN MA NO. 23 P/HUM/2024 ATAS KEBERADAAN PUTUSAN MK NO. 70/PUU-XXII/2024 DALAM OBJEK PENGUJIAN BATAS USIA PENDAFTARAN PENCALONAN PILKADA SERENTAK NASIONAL 2024 - Widokarti, Fenny Eka; Juanda, Juanda; Ambarwati, Ambarwati (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The normative contradiction between Supreme Court Decision Number 23 P/HUM/2024, which raised the age limit for regional head candidates, and Constitutional Court Decision Number 70/PUU-XXII/2024, which precisely nullified the norm regarding the minimum age limit, creates legal uncertainty and potential serious implications for the organization of the Regional Head Elections (Pilkada). This research employs a descriptive analytical method with a normative juridical approach to analyze the legal validity of Supreme Court Decision No. 23 P/HUM/2024 in relation to Constitutional Court Decision No. 70/PUU-XXII/2024 concerning the age limit for candidacy in the 2024 National Simultaneous Regional Head Elections. This approach primarily focuses on the study of library legal materials (secondary sources), which include primary legal materials such as the 1945 Constitution, laws pertaining to the Supreme Court and Constitutional Court, and relevant Supreme Court and Constitutional Court decisions. It also incorporates secondary legal materials in the form of legal scholars' opinions. Data collection was carried out through a literature review (document study), supplemented by limited field study, and analyzed using a qualitative juridical method to formulate answers to the existing legal issues. The research findings indicate that the Supreme Court's (MA) decision regarding the age limit for candidacy registration in the 2024 National Simultaneous Regional Head Elections (Pilkada) lacks binding legal force and there's no legal basis for the MA to review provisions stipulated by Law No. 10/2016 concerning Pilkada. In this instance, the MA has exceeded its authority. Consequently, the legal validity of the MA's decision, in light of the Constitutional Court's (MK) decision on the age limit for Pilkada candidacy registration, is deemed legally invalid under applicable laws and regulations. Therefore, with the MA's decision being invalid, the Constitutional Court's decision is the one that prevails.